Enhanced Piezoelectric Properties and Thermal Stability in the (K0.5Na0.5)NbO3:ZnO Lead‐Free Piezoelectric Composites. Issue 12 (7th September 2015) - Pan, Zhao; Chen, Jun; Fan, Longlong; Zhang, Ji; Zhang, Shantao; Huang, Yu; Liu, Laijun; Fang, Liang; Xing, Xianran
Abstract : The piezoelectric properties of (K0.5 Na0.5 )NbO3 (KNN) are normally enhanced by chemical substitutions or doping to form solid solutions. In this study, we report that the piezoelectric properties of KNN and thermal stability of piezoelectric coefficient d 33 can be both enhanced by forming the composite of KNN:ZnO. The d 33 of KNN:0.2ZnO can be improved to 110 pC/N by introducing the ZnO nanoparticles, which is better than the pure KNN ( d 33 = 85 pC/N). The Curie temperature ( T C = 407°C) remains well comparable to the pure KNN ( T C = 408°C). Furthermore, the thermal stability of both remanent polarization ( P r ) and piezoelectric parameter ( d 33 ) is improved. The enhanced thermal stability could be related to the induced built‐in electric field or the enhanced sinterability by the addition of ZnO. The present results may help to optimize the piezoelectric properties of lead‐free materials by forming composite.